Analisis Praktik Klinik Keperawatan pada Pasien St Elevasi Miokard Infark (STEMI) Anterior dengan Inovasi Intervensi Isometric Handgrip Exercise untuk Menurunkan Tekanan Darah - Handayono, Priyo; Safrudin, Bachtiar; Wibowo, Thomas Ari; Rizal, Alfi Fakhrur (Wiraraja Medika : Jurnal Kesehatan, 2024)
If hypertension is not treated for a long time, it will cause dangerous complications such as stroke, heart attack, heart failure, chronic kidney failure and eye damage (hypertensive retinopathy). One of the non-pharmacological treatments for hypertensive patients is by providing isometric handgrip exercise therapy. The aim of the research was to conduct an analysis of nursing clinical practice in anterior ST elevation myocardial infarction (STEMI) patients using the innovative intervention of isometric handgrip exercise to reduce blood pressure in the ICCU room at Aji Muhammad Parikesit Tenggarong District Hospital. This research method is a One-Shot Case Study, namely a research design where the researcher only carries out one treatment which is thought to have had an effect and then carries out a post-test. The patient in this study was 1 person with the characteristics of a patient diagnosed with a medical diagnosis of ACS Stemi who had high blood pressure. The results of the implementation of isometric handgrip exercise therapy to reduce blood pressure showed significant results during the 3 interventions in which blood pressure was reduced. The conclusion from the results of the analysis carried out showed that there was a change in blood pressure after being given the isometric handgrip exercise intervention